(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
This study presents an investigation conducted on beeswax as a law temperature phase change material for thermal energy storage. Thermal energy storage technologies has the potentials of leading to sustainability in energy especially as it relates to solar energy and waste heat recovery both for high and low temperature applications. Beeswax has been identified with the potentials of being used in Thermal energy storage (TES). This research investigated the thermal stability and life cycling of three samples of beeswax from different nesting ecology. Differential scanning calorimetry (DSC), thermo-gravimetric analysis (TGA) and differential thermal analysis (DTA) were used to determine their suitability for use in low temperature thermal energy storage application. The result obtained showed the stability of beeswax within operating temperatures of 60oC to 270oC, 60oC to 260oC and 60oC to 250oC for samples A, B and C. Life cycling analysis using Coffin Mason equation showed that the material can survive for 34.76 service years within the beeswax stable temperature region. Hence, beeswax can be used in low temperature heat storage applications.